2007
DOI: 10.1016/j.janxdis.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms in trauma-exposed college students: The role of trauma-related cognitions, gender, and negative affect

Abstract: Considerable evidence indicates a prominent role for trauma-related cognitions in the development and maintenance of posttraumatic stress disorder (PTSD) symptoms. The present study utilized regression analysis to examine the unique relationships between various trauma-related cognitions and PTSD symptoms after controlling for gender and measures of general affective distress in a large sample of trauma-exposed college students. In terms of trauma-related cognitions, only negative cognitions about the self wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
74
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 41 publications
25
74
2
3
Order By: Relevance
“…world/self-blame; Bryant & Guthrie, 2005;Foa & Rauch, 2004;Moser, Hajcak, Simons, & Foa, 2007). This result is not surprising, given substantial conceptual overlap between negative self-related cognition, and symptoms, as well as with our other key variables.…”
Section: Discussionmentioning
confidence: 66%
“…world/self-blame; Bryant & Guthrie, 2005;Foa & Rauch, 2004;Moser, Hajcak, Simons, & Foa, 2007). This result is not surprising, given substantial conceptual overlap between negative self-related cognition, and symptoms, as well as with our other key variables.…”
Section: Discussionmentioning
confidence: 66%
“…The importance of gender in PTSD is reflected in the robust finding that women are more prone to develop PTSD than men (see Tolin & Foa, 2006 for review). Indeed, Moser and colleagues have found that the SELF factor remained associated with PTSD severity even after statically controlling for gender, while this was not the case for the WORLD and the BLAME factors (Moser, Hajcak, Simons, & Foa, 2007). In this paper we further examine the relation between posttraumatic cognitions and PTSD severity for men and women separately.…”
Section: Introductionmentioning
confidence: 82%
“…Men and women tend to experience different types of A1 events but, even after controlling for type of experienced A1 event, the gender differences in PTSD prevalence remain (Christiansen & Hansen, 2015; Moser, Hajcak, Simons, & Foa, 2007; Tolin & Foa, 2008). It is still unknown whether the increased vulnerability in women to develop PTSD after experiencing A1 events also extends to the experience of non-A1 events.…”
Section: Introductionmentioning
confidence: 99%